Lasiodiplodia theobromae causing seedling and leaf blight in coconut: an opportunistic pathogen exploiting host stress in nursery and field conditions - Rao, V Govardhan; Naidu, M Mutyala; Anoosha, V; Kireeti, A; Sumitha, S; Jerard, B Augustine (Indian Journal of Plant Protection, 2025)
Lasiodiplodia theobromae (syn. Botryodiplodia theobromae), though typically considered a weak or opportunistic pathogen, is increasingly recognized as a major threat to coconut cultivation, particularly under stress conditions such as high humidity, drought, poor drainage, and nutrient imbalance. It causes seedling blight, leaf blight, and nut rot, leading to yield losses of up to 25%. Given the economic significance and long gestation period of coconut, early-stage infections can severely reduce plant vigor and productivity. The rising incidence of this disease is attributed to climate variability and inadequate nursery management practices. In this study, L. theobromae isolates from Andhra Pradesh were characterized morphologically, culturally, and molecularly using ITS region sequencing. Observations included colony morphology, pigmentation, spore size, and fruiting structures. Pathogenicity was confirmed through artificial inoculation techniques. The pathogen, primarily spread through pycnidia and conidia on infected debris, soil, and tools, thrives under humid and poorly drained conditions. An in vitro fungicide screening at 100, 250, and 500 ppm demonstrated complete mycelial inhibition by Carbendazim, Tebuconazole + Captan, Prochloraz + Tricyclazole, Tebuconazole + Trifloxystrobin, and Azoxystrobin + Tebuconazole + Prochloraz. Other fungicides such as Tebuconazole (Bounos), Propiconazole (Tilt), and Fluopyram + Tebuconazole showed dose-dependent efficacy. Field trials conducted over two seasons at Dr. YSRHU–HRS, Ambajipeta, revealed that spraying Carbendazim (1 g/l) followed by Potassium Sulphate (5 g/l) in alternate weeks provided the highest disease suppression (81.49–79.15%). Treatments with Copper Oxychloride, Hexaconazole, and Propiconazole combined with SOP were moderately effective.